Diversity of aquatic macroinvertebrates along creeks with different riparian cover in Murocomba Protector Forest, Ecuador - Urdanigo, Juan Pablo; Díaz Ponce, Mariela; Tay-Hing Cajas, Carolina; Sánchez Fonseca, Carlos; Yong Benitez, Ronny; Armijo Albán, Katherine; Guerrero Chúez, Norma; Mancera-Rodríguez, Néstor Javier (Revista de Biología Tropical, 2019)
Land-use change from native forests to agriculture, livestock and exotic forest plantations is a main factor affecting riparian vegetation and aquatic communities. The aim of this study was to assess responses of aquatic macroinvertebrate assemblages to riparian cover change in Murocomba protective forest, Valencia, Ecuador. Aquatic macroinvertebrates were collected and physicochemical variables were measured during dry (June-October 2014) and rainy (December-April 2015) seasons along three creeks with different riparian cover: native forests Q1-CBN, pasture for agricultural and livestock activities Q2-CAG, and exotic forest plantations Q3-CPF. According to the Macroinvertebrate Family Biotic Index (FBI) and the Biological Monitoring Working Party Index (BMWP/Col) the best conditions existed in the creek Q1-CBN, while the Ephemeroptera, Plecoptera and Trichoptera Index (EPT) decreased in the creek Q2-CAG during the rainy season. The Shannon-Weaver index showed higher values in Q1-CBN and Q3-CPF in the dry period, and the dominance increased in the Q3-CPF in rainy season. A total of 6 583 macroinvertebrates were collected. Trichoptera was the most abundant order and Hidropsychidae the most abundant family. The Coleoptera order showed greater abundance in Q1-CBN and Diptera in Q2-CAG, while Hemiptera showed the lowest abundance in Q3-CPF. Psephenidae, Chironomidae, Leptophlebiidae, Veliidae, Simuliidae, Baetidae and Leptohyphidae were associated with the highest values of total dissolved solids and pH, as well as higher values of IBF and lower values of EPT, BMWP, and depth of the channel in Q2-CAG, whereas Leptoceridae, Elmidae, Ptilodactylidae and Philopotamidae were associated with higher values of EPT, BMWP and depth of the channel in Q1-CBN and Q3-CPF. A negative influence of anthropic activities on the physicochemical variables and structure of the macroinvertebrate assemblages was evidenced. This indicates that the riparian vegetation is a factor that determines the establishment and structure of aquatic communities.